Contradictions and their consequences: how competing policy mandates facilitate use of a punitive framework in domestic violence-child maltreatment cases - Armstrong, Elizabeth Marie (Child maltreatment, 2021)
Research shows child welfare cases involving caregiver domestic violence (DV) continue to produce punitive consequences for non-abusive adult victims. This occurs despite the adoption of a supportive policy framework that emphasizes perpetrator responsibility for DV-related harm to children. Risk assessment procedures have been implicated in punitive outcomes, but we know little about how they shape child welfare workers? decision-making practice. Focusing on a state with a supportive policy framework, this paper uses grounded theory to examine how policy contradictions, procedural directives around risk assessment, and informal interventions produce punitive consequences for adult victims of DV and unmitigated risk to children. Data include state policy and procedural documents and interviews with child welfare workers describing decision-making in their most recent completed case and most recent case involving DV. Findings point to the need for active alignment of policies and procedures, greater integration of knowledge across practice areas, renewed commitments to differential response, and greater inclusion of DV specialists in child welfare settings.